PROBLEMS OF ETHNO-POLITICAL HISTORY OF THE TRIBAL UNION OF THE AS IN ANCIENT IN CENTRAL ASIA (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
Ethnic and political history of As in the ancient times is connected with their wars for domination in Central Asia with Huns. Having suffered defeat at the hands of Mode-Shanyu, the As (Big Yuezhi) moved from Gansu to Semirechye. Later part of As founded Kushan kingdom, and the other part of them remained in Semirechye and became a part of Usun state
Keywords: As, Az, big Yuezhi, Semirechye, Huns, Usuns